Extending the decision-making capabilities in remanufacturing service contracts by using symbiotic simulation - Silva Teixeira, Evandro Leonardo; Tjahjono, Benny; Absi Alfaro, Sadek Crisóstomo; Wilding, Richard D. (Elsevier, 2019)
Remanufacturing is a critical enabler of a resource efficient manufacturing industry that has long been associated with high value products. Over time, the commercial relationship between customers and service providers has been made through the fulfilment of rights and obligations under remanufacturing service contracts. Nonetheless, financial analysis to evaluate the contract terms and conditions are becoming increasingly difficult to conduct due to complex decision problems inherent in remanufacturing systems. In order to achieve better and safer decision-making to shape the business strategies, remanufacturers often employ computer-based simulation tools to assess contractual obligations and customers’ needs. This paper discusses the roles of a symbiotic simulation system (SSS) in supporting decision-making in remanufacturing systems. An industrial case study of power transformer remanufacturing illustrates how SSS can support contract remanufacturers in managing service contracts planning and execution. By linking the simulation model to the physical system, it has been demonstrated that the capabilities of the remanufacturers to make critical decisions throughout the entire service contract period can be extended.
Keywords: Service contract; Symbiotic simulation; Remanufacturing; Decision-making